2003
DOI: 10.1007/s00572-003-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza of plants in different vegetation types in tropical ecosystems of Xishuangbanna, southwest China

Abstract: We examined plants growing in four tropical vegetation types (primary forest, secondary forest, limestone forest and a slash and burn field) in Xishuangbanna, southwest China for mycorrhizal associations. Of the 103 plant species examined (belonging to 47 families), 81 had arbuscular mycorrhizal (AM) associations, while three species possessed orchid mycorrhiza. AM colonization levels ranged between 6% and 91% and spore numbers ranged between 1.36 spores and 25.71 spores per 10 g soil. Mean AM colonization lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 2 publications
9
31
1
2
Order By: Relevance
“…The AM status of Cyperaceae was found to vary in different habitats of China. Muthukumar et al (2003) found no mycorrhizal structures in three sedge species in the Yunnan province. In contrast, most of 22 ecotypes examined in nine sedge species from Tibetan grasslands were mycorrhizal (Gai et al 2005).…”
Section: Mycorrhizal Status Of Plantsmentioning
confidence: 90%
See 2 more Smart Citations
“…The AM status of Cyperaceae was found to vary in different habitats of China. Muthukumar et al (2003) found no mycorrhizal structures in three sedge species in the Yunnan province. In contrast, most of 22 ecotypes examined in nine sedge species from Tibetan grasslands were mycorrhizal (Gai et al 2005).…”
Section: Mycorrhizal Status Of Plantsmentioning
confidence: 90%
“…Some 120 agricultural plant species, including grain, oil, and economic crops and horticultural and Chinese medicinal plants, have been found to form associations with AMF (Table 1). In addition, wild plants inhabiting a range of environments, such as heathland, mountain areas, grasslands, woodlands, and tropical forests, were also surveyed (Gong et al 1997;Gai et al 2000a;Zhao 2000;Chen et al 2001;Zhao et al 2001bZhao et al , 2003Wang and Liu 2002;Muthukumar et al 2003;Bao and Yan 2004;Ding et al 2004). Mycorrhizal incidence among wild herbaceous plants is consistently high, with over 90% of the species examined (about 300) exhibiting AMF colonization, and AM associations also occur in trees and shrubs of certain climatic zones.…”
Section: Mycorrhizal Status Of Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…AM associations are widespread, occurring in the roots of most angiosperms and pteridophytes, along with some gymnosperms and the gametophytes of some lower plants such as mosses and lycopods (Smith and Read 1997). Recent studies have indicated that AM fungi are common and ecologically important in tropical ecosystems, and that cooccurring plant species vary considerably in their germination, growth, and flowering responses to mycorrhizal colonization along a continuum from highly responsive obligately mycotrophic species to facultatively mycotrophic and nonresponsive species (Johnson et al 1997;Muthukumar et al 2003). Tropical rain forests display high plant species diversity and complex community structure (Read 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in the arbuscular mycorrhizae of tropical rain forest plants (Guadarrama and Alvarez-Sanchez 1999;Muthukumar et al 2003;Tawaraya et al 2003;Zhao 2000;Zhao et al 2001). However, according to Brundrett et al (1995) and Wubeta et al (2003), apart from a few fragmented reports, there have been no investigations reported on arbuscular mycorrhizae of the family Meliaceae.…”
Section: Introductionmentioning
confidence: 99%